Stilbene biosynthesis and gene expression in response to methyl jasmonate and continuous light treatment in Vitis vinifera cv. Malvasia del Lazio and Vitis rupestris Du Lot cell cultures. Issue 2 (10th September 2018) - Donati, Livia; Ferretti, Luca; Frallicciardi, Jacopo; Rosciani, Roberta; Valletta, Alessio; Pasqua, Gabriella
Abstract : Vitis rupestris is used as rootstock or to obtain hybrids with Vitis vinifera, due to its resistance to certain pathogens. Its resistance mechanisms are poorly understood, while it is known that stilbene neo‐synthesis is a central defense strategy in V. vinifera . In the present study, the response to methyl jasmonate (MeJa) and light treatment in terms of stilbene biosynthesis and the expression of genes involved in polyphenol biosynthesis was investigated in V. vinifera and V. rupestris cells. The two species exhibited a similar constitutive stilbene content [2.50–2.80 mg g −1 dry weight (DW)], which greatly increased in response to elicitation (8.97–11.90 mg g −1 DW). In V. vinifera, continuous light treatment amplified the effect of MeJa, with a stilbene production that had never previously been obtained (26.49 mg g −1 DW). By contrast, it suppressed the effect of MeJa in V. rupestris . Gene expression was consistent with stilbene production in V. vinifera, whereas discrepancies were recorded in V. rupestris that could be explained by the synthesis of stilbenes that had never before been analyzed in this species.